ANALISIS UPAH SISTEM BAGI HASIL ANAK BUAH KAPAL PADA PERAHU PENANGKAP IKAN DI KABUPATEN LAMONGAN - Trischa Relanda Putra (Trunojoyo University of Madura, 2017)
Sea fisheries have a very important role in the civilization of human development (Fauzi, 2010:1). Marine fisheries management requires production costs to obtain goods and services.Every production is always faced with cost problems, capital, and wages.Wages in the primary sector use a profit-sharing system.The purpose of this study is to describe and analyze the wage system for large size boat in Brondong and Blimbing urban villages. This study uses qualitative research methods, grounded theory design, observation data collection, interviews, documentation, and documents. It uses analytical techniques such as data reduction, data presentation, and conclusions. It also use source triangulation to test the validity of the data. The results of this study show that profit sharing system is not the same among skipper to one another, but in essence all meet the wage ≥ 40%.